2022
DOI: 10.3390/ijms232113125
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Isorhamnetin Reduce Benzo[a]pyrene-Induced Genotoxicity by Inducing RAD51 Expression through Downregulation of miR−34a

Abstract: Benzo[a]pyrene (B[a]P) is metabolized in the liver into highly reactive mutagenic and genotoxic metabolites, which induce carcinogenesis. The mutagenic factors, including B[a]P-7,8-dihydrodiol-9,10-epoxide (BPDE) and reactive oxygen species, generated during B[a]P metabolism can cause DNA damage, such as BPDE-DNA adducts, 8-oxo-dG, and double-strand breaks (DSBs). In this study, we mechanistically investigated the effects of quercetin and its major metabolite isorhamnetin on the repair of B[a]P-induced DNA DSB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Therefore, the roles of miR-33, and miR-34a in cholesterol metabolism may be potential biomarkers in atherosclerosis. Recently, Kim et al (2022) have reported that quercetin and its metabolite, isorhamnetin, suppress liver DNA damage via miR-34a downregulation in HepG2 cells. However, QN’s effects on the regulatory mechanisms of miR-33 and miR-34a in the liver of HC diet-fed mice are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the roles of miR-33, and miR-34a in cholesterol metabolism may be potential biomarkers in atherosclerosis. Recently, Kim et al (2022) have reported that quercetin and its metabolite, isorhamnetin, suppress liver DNA damage via miR-34a downregulation in HepG2 cells. However, QN’s effects on the regulatory mechanisms of miR-33 and miR-34a in the liver of HC diet-fed mice are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analyses were performed adhering to previous research [ 51 , 52 ]. Gene ontology (GO) analysis of DEGs (fold change ≥ 2; normalized log 2 ≥ 5) was performed.…”
Section: Methodsmentioning
confidence: 99%